Allelopathy: as an ancestral alternative for pest control in family orchards - Rojas Basto, Laura Constanza
Soils and their biodiversity have been seriously affected by the unconscious use ofagrochemicals for a long time, which has affected ecosystems. Therefore, agroecologyproposes the use of allelopathy as a sustainable alternative to control and counteract pests inurban gardens. With this agroecological strategy, the control of spontaneous species has beensought using plant parts with herbicide activity. The present work consists of bibliographicalresearch that aims to compile scattered information in several articles on the biodiversity ofmedicinal plants with herbicide potential. For the research, it was decided to search for articlesin national and international journals during the period from 2000 to 2022